The Effect of Giving Oxygenic Probiotics with Different Doses On the Growth and Survival of Striped Catfish (Pangasius hypophthalmus) with an aeration system - Simanjuntak, Josua Naiktua; Mulyadi, Mulyadi; Pamukas, Niken Ayu (Department of Aquaculture, Faculty of Fisheries and Marine Universitas Riau, 2026)
Striped catfish is the leading commodity for freshwater aquaculture in Indonesia because of its high economic value, rapid growth, high protein content, and low cholesterol. However, intensive aquaculture systems often degrade water quality due to the accumulation of feed residues and metabolites, which triggers stress, lowers immunity, and increases mortality. One solution is the use of oxygenic probiotics containing Nitrosomonas, Nitrobacter, Rhodobacter, and Saccharomyces to decompose ammonia and improve fish digestion. The effectiveness of probiotics is influenced by the dosage of application. The research was conducted in March 2025 at the Cultivation Technology Laboratory, Universitas Riau, using a one-factor Complete Random Design with four levels of treatment (P0 = control, P1 = 1.5 mL/L, P2 = 2.5 mL/L, P3 = 3.5 mL/L, P4 = 4.5 mL/L) and three replicates for 30 days. The results showed P3 as the best treatment with an absolute weight of 4.44±0.03 g, an absolute length of 3.41±0.01 cm, a specific growth rate of 4.37±0.05%, a survival rate of 95.5±3.85%, and an FCR of 1.32±0.005. Water quality parameters: temperature 25.86–29°C, pH 6.1–8.1, DO 4.1–7.2 mg/L, and ammonia 0.003–0.168 mg/L.